A STUDY OF DRUG UTILIZATION IN PATIENTS OF CARCINOMA BREAST RECEIVING SYSTEMIC CHEMOTHERAPY IN TERTIARY CARE HOSPITALS - SHAH, SUCHI; SINGH, ANIL; MUNDHAVA, SHAILESH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study is to study drug utilization in patients with breast carcinoma receiving systemic chemotherapy in government as well as private set-up. Methods: This was a record-based, retrospective-prospective study, analyzing the prescription pattern of drugs used for systemic chemotherapy in patients diagnosed with carcinoma breast at government teaching hospital (GTH) and private trust hospital (PTH) for 1 year in 600 patients. Patient’s demographic, clinical, and therapeutic data were collected from the files and personal interviews and analyzed in Microsoft Excel. Results: Diagnosis of breast carcinoma was highest in age bracket of 40–49 years (32.33% GTH and 32.67% PTH), and the most common presenting symptom was painless lump (76.33% GTH and 83% PTH). In GTH, most frequently prescribed regimen was 4AC → 4T → RT (17.33%). In PTH, most commonly prescribed regimen was 6FEC → RT (19.33%). Highest prescribed drugs were A (32.8%), C (29.12%), and F (20.24%) in GTH and A (32.26%), F (31.68%), and E (16.45%) in PTH. Average number of drugs prescribed per prescription was 12.55 and 11.37; percentage of chemotherapeutic agents prescribed by generic name was 100 and 95.02, and from the WHO essential drug list (2015) was 96.43 and 82.77 in GTH and PTH, respectively (A= Cyclophosphamide, C= Doxorubicin, T=Taxanes [Paclitaxel/Docetaxel], F=5-fluorouracil, E=Epirubicin, RT=Radiotherapy, → followed by, the number indicates chemotherapy cycle). Conclusion: The study results can help in generating local data regarding drug use pattern of the systemic chemotherapeutic agents in breast cancer patients and promote rational drug use.